Hubungan Paparan Kebisingan Dengan Gangguan Pendengaran Pada Pekerja Industri Kerajinan Pandai Besi Di Desa Hadipolo Kecamatan Jekulo Kabupaten Kudus - Rusiyati, Rusiyati; Nurjazuli, Nurjazuli; Suhartono, Suhartono (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2012)
Background : This study describes the correlation between noise exposure and hearing loss on workers at craftsmithy, Hadipolo,Jekulo, Kudus.Methode: The study is an observational cross-sectional approach. The number of sample is 79 respondents from79 craft smithies. Data were collected by interviewing respondents, measuring the intensity of noise in the smithycrafts and examining the workers’ hearing before and after working with audiometry. Data analysis was taken byunivariate, bivariate statistics with Kendall’s Tau test and Wilcoxon Signed RanksTest.Result : The results obtained of 79 craft smithy that was by measuring noise that are included in impulsive noiseis 72 (91.1%) work site noise intensity equal to exceeding NAB.And the lowest noise intensity of 72 dB and a peakintensity of 99 dB, average 92.38 dB, the standard deviation is 5.86 ,medianis 94dB. Audiometric test results onthe right ear before working respondents, the mean value of 24.68 dB with a standard deviation of 8.86 dB andafter work mean value 30.57 dB, 14.64 dB standard deviation. Meanwhile, the left ear before working respondents,the mean standard deviation of 11.30 dB 24.19 dB, and after working with the mean standard deviation of 15.12dB 28.73 dB. Thus, the mean audiometric test results both before and after working on the right ear and left earincreased.The conclusion with Kendall’s Tau test is 95% CI significant p value indicates the p value of 0.076 (p >0.05) for the right ear before work, which means there is no significant correlation between the intensity of noisewith hearing loss right ear and left ear before work, p value 0.021 (p < 0.05), which means that there is ameaningful relationship. And working conditions after the right ear showed significant value, p value 0.121 (p>0.05), which means there is no significant correlation between the intensity of the noise with hearing loss rightear. And for the left ear obtained p value 0.05 (p = 0.05), which means that there is a significant correlationbetween the intensity of noise with hearing loss left ear after work. For the Wilcoxon Signed Ranks Test with a levelof 95%, proving that for the right ear and left their values obtained p value = 0.000 (P <0.05), there is asignificant difference to the results of audiometric measure the right and left ear respondents in conditions beforeand after work.Keywords: A Craft smithy, Noise, Hearing Loss